The Use of Levels One and Two Dermatoglyphics for Sex Identification in University of Ibadan Community, Southwest Nigeria (Nigerian Journal of Physiological Sciences, 2023)
Dermatoglyphic traits are genetically determined and remain constant until death. Dermatoglyphics features are arranged from patterns, minutiae and ridgeology. This study utilized patterns and minutiae details of fingerprints as a means of sexual differentiation amongst the University of Ibadan community. Three hundred and eighty-four (192 males and 192 females) participants from the University of Ibadan community were recruited using multistage sampling technique. Fingerprints were obtained using fingerprint scanner Dermalog LF10, Hamburg, Germany. GraphPad Prism 7.0 was used for the test of mean of variables. Ulnar loop, whorl and radial loop patterns were found to be predominantly distributed in both male and female in that order. However, the arch pattern was significantly different between female and male. The male subjects had significantly higher total finger ridge count (TFRC). All the analysed minutiae were significantly different between male and female except bridge. The arch pattern, TFRC and level 2 details (minutiae) of dermatoglyphics could be used as markers for sexual differentiation.